Character introductions in oral narratives of Swedish–German bilingual preschoolers. Issue 2 (April 2022) - Lindgren, Josefin; Reichardt, Valerie; Bohnacker, Ute
Closely related Swedish and German both mark information status of referents morphologically, though little is known about its acquisition. This study investigates character introductions in the narratives of 4- and 6-year-old Swedish–German bilinguals ( N = 40) in both languages, elicited with MAIN Cat/Dog . We analyse effects of age group, language and animacy (human vs nonhuman characters) on the type of referring expression (indefinite NP and pronoun), as well as effects of language proficiency and exposure on the use of indefinite NPs for each language. We also explore which syntactic constructions indefinite NPs occur in. A significant difference was found between the two age groups, but not between languages. No effect was found of language skills or exposure. Four-year-olds used more pronouns and a lower proportion of indefinite NPs than 6-year-olds. Pronouns were more frequent for the human character than for nonhuman animate characters. Whilst animacy (humanness) promoted the use of pronouns, it did not affect the choice of morphological form for lexical NPs (indefinite/definite). The age groups differed in how indefinite NPs were used. Four-year-olds produced fewer narrative presentations (where a character is introduced as part of a typical story opening, e.g. Once upon a time there wasa cat ) than 6-year-olds, and more labellings (with only an NP, or a clausal predicative, e.g. That'sa cat ). Qualitative analyses suggest that the children's indefinite NPs in labelling constructions can be both referential (when setting the narrative scene), and type-denoting (when naming referents in individual pictures). Whilst the children's abilities to introduce story characters develop measurably from 4 to 6 years in Swedish and German, appropriateness of character introductions not only depends on whether an indefinite NP is chosen, but also on the syntactic construction this indefinite NP is used in.